Association between Obesity and COVID-19: Insights from Social Media Content - Alotaibi, Mohammed; Pai, Rajesh R.; Alathur, Sreejith; Chetty, Naganna; Alhmiedat, Tareq; Aborokbah, Majed; Albalawi, Umar; Marie, Ashraf; Bushnag, Anas; Kumar, Vishal (Information (Basel), 2023)
The adoption of emerging technologies in healthcare systems plays a crucial part in anti-obesity initiatives. COVID-19 has intensified the Body Mass Index (BMI) discourses in AI (Artificial Intelligence)-powered social media. However, few studies have reported on the influence of digital content on obesity prevention policies. Understanding the nature and forums of obese metaphors in social media is the first step in policy intervention. The purpose of this paper is to understand the mutual influence between obesity and COVID-19 and determine its policy implications. This paper analyzes the public responses to obesity using Twitter data collected during the COVID-19 pandemic. The emotional nature of tweets is analyzed using the NRC lexicon. The results show that COVID-19 significantly influences perceptions of obesity; this indicates that existing public health policies must be revisited. The study findings delineate prerequisites for obese disease control programs. This paper provides policy recommendations for improving social media interventions in health service delivery in order to prevent obesity.